2011
DOI: 10.1016/j.juro.2010.11.090
|View full text |Cite
|
Sign up to set email alerts
|

Routine Adrenalectomy Is Unnecessary During Surgery for Large and/or Upper Pole Renal Tumors When the Adrenal Gland Is Radiographically Normal

Abstract: INTRODUCTION AND OBJECTIVES Concurrent adrenalectomy during renal surgery for RCC was once routine. More recent data suggest that adrenalectomy should be reserved for tumors ≥7cm, particularly those involving the upper pole. We evaluated the radiographic and pathologic incidence of adrenal involvement in patients undergoing renal surgery for RCC ≥7cm. METHODS Patients undergoing renal surgery for tumors ≥7cm between 1999 and 2008 were identified from our kidney cancer registry. Fisher’s exact test was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
1
17
0
4
Order By: Relevance
“…Similar to the study by Kutikov and colleagues, 1 Weight et al 2 from the Mayo Clinic reported on a large cohort of 4,018 patients, and found ipsilateral adrenal involvement in only 88 patients (2.2%). Adrenal involvement was present in 42 (3.4%) of 1,229 patients with upper-pole tumors versus 46 (1.6%) of 2,789 patients with renal tumors in other locations.…”
supporting
confidence: 73%
See 3 more Smart Citations
“…Similar to the study by Kutikov and colleagues, 1 Weight et al 2 from the Mayo Clinic reported on a large cohort of 4,018 patients, and found ipsilateral adrenal involvement in only 88 patients (2.2%). Adrenal involvement was present in 42 (3.4%) of 1,229 patients with upper-pole tumors versus 46 (1.6%) of 2,789 patients with renal tumors in other locations.…”
supporting
confidence: 73%
“…Recent articles by Kutikov et al 1 from the Fox Chase Cancer Center and Weight et al 2 from the Mayo Clinic examine the role of a routine adrenalectomy for patients with renal cell carcinoma (RCC). Both articles provide compelling arguments against the routine removal of the adrenal gland and present strong data supporting their points.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have questioned the role of routine adrenalectomy during radical nephrectomy. The most recent series of 179 patients with tumors greater than 7 cm demonstrated that adrenal involvement is quite rare and was observed in only 4.4% of these patients [7]. In those who had adrenal involvement, preoperative imaging was 100% specific in detecting this preemptively, with 100% negative predictive value.…”
Section: Localized Large Renal Tumorsmentioning
confidence: 99%